2001
DOI: 10.1097/00002820-200112000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Pain Education: A Structured Clinical Instruction Module for Hospice Nurses

Abstract: The learning experience with the Cancer Pain Structured Clinical Instruction Module (SCIM), a highly structured skills training course for medical students, has been reported favorably. The purpose of this study was to present the Cancer Pain SCIM to registered nurses employed in a hospice setting. The goal of the study was to pilot test a structured cancer pain educational program for hospice nurses and to determine the perceived effectiveness of this course on the participants' cancer pain assessment and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…For instance, positive outcomes have been reported from nurses who participated in a highly structured clinical training course providing education in cancer pain (Plymale et al, 2001). There is some evidence from small-scale studies to suggest that interprofessional education across primary and secondary care may assist in improving the delivery of symptom control for cancer patients (Leslie et al, 2003).…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
“…For instance, positive outcomes have been reported from nurses who participated in a highly structured clinical training course providing education in cancer pain (Plymale et al, 2001). There is some evidence from small-scale studies to suggest that interprofessional education across primary and secondary care may assist in improving the delivery of symptom control for cancer patients (Leslie et al, 2003).…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
“…We have delivered the SCIM workshop with less facilitators than described in other studies, 8,12,14 and utilized nonspecialist staff in the successful delivery of the program. We now have a core of involved teachers that enjoy the experience and offer to be involved with each new group.…”
Section: Discussionmentioning
confidence: 99%
“…8 They have been used in the teaching of pain management, cancer care, and surgical techniques and have been evaluated as an effective, sustainable tool delivering durable skills and knowledge improvements. [9][10][11][12] To date, this literature has focused on the use of SCIMs to teach various aspects of a single topic. The SCIM program developed for the palliative care attachment is novel, as it covered numerous aspects of knowledge and skills essential for end-of-life care.…”
Section: Description Of the Scim Workhopmentioning
confidence: 99%
“…Educational programs for students and residents have shown improved knowledge and attitudes toward the management of pain, including the proper use of opioids [20,29,[32][33][34]. Postworkshop surveys from residents in this study showed that their beliefs and concerns about using opioids for chronic low back pain were changed by participating in a 4-hour interactive session using short didactics, observation exercises with reflection, and practice with feedback using patient actors [35].…”
Section: ± 231mentioning
confidence: 94%